Static Ups System Using Dual Power Source and Wireless Control - Nor Azriq Ilham Nor Azmi,; Azuwien Aida Bohari, (Progress in Engineering Application and Technology, 2026)
Uninterruptible Power Supply (UPS) systems are important in providing continuous power for sensitive electrical equipment during power interruptions or outages. However, conventional UPS systems rely heavily on grid power. This project aims to design and develop a static UPS system using dual power sources consisting of grid supply and solar energy, intergrated with wireless monitoring and control capability. The system incorporates a solar charge controller, battery bank, inverter, automatic switch, and Wi-Fi-enabled smart breakers to ease the power transfer and remote operation. Hardware assembly were carried out, followed by performance testing under different operating conditions. Experimental results show reliable automatic source switching, stable output voltage, effective battery charging, and successful real-time monitoring and remote control. In conclusion, the proposed hybrid static UPS improves power reliability, reduces grid dependency, and provides a practical and cost-effective solution for small-scale residential and commercial applications.